A novel polyether polyol contains repeating cyclohexane units and its application on reactive polyurethane adhesive. (26th June 2020) - Zong, Hongliang; Fang, Cheng; Lin, Zhongxiang; Yan, Qiming; Lin, Xing
Abstract : A novel polyether polyol was successfully synthesized from cyclohexene oxide (CO), propylene oxide (PO), and poly(propylene glycol) 400 through ring‐opening polymerization, catalyzed by double metal cyanide catalyst for the first time. Then, the obtained cyclohexane‐based polyether polyol (CPOL) further reacted with 4, 4′‐diphenylmethane diisocyanate to form reactive polyurethane adhesive (RPUA). The thermal properties and mechanical strength of the RPUA were characterized by differential scanning calorimetry, dynamic mechanical analysis, thermogravimetric analysis, and lap shear strength test. It was found that with the introduction of cyclohexane units, the glass transition temperature ( T g ) and thermal stability of the RPUA increased about 122.3% and 3.32%, respectively. Besides, the lap shear strength of the RPUA prepared with the synthesized CPOL was 130.67% higher than the counterpart derived from conventional polyether polyol 2000. Furthermore, compared with RPUA‐PPG, RPUA‐CPOL also exhibited excellent lap shear strength on polycarbonate substrate even when the adhesion joints were immersed into hot water or alkaline solvent. All the above results suggest that the cyclohexane units in polyether polyol have great improvements in the thermal stability and lap shear strength of RPUA.